(3WQS GdCNHGQ HeG LQi BNQ GdCQHYjf ef GdbQf GdKGdK YTQ ddoeSdejf ef GdcaGQ hYJh GdMGL YHOGdbGOQ hCgd OGFQI GdaLGQs - (3eMeO GdYQHj Hf YHO GdbGOQ GdeTQbj GdZQjSjs
(3ChdgG (B:s
(3ajYde GdhGba Ydjg Gfg deG TGY YfO GdNGU hGdYGe TJe ef JMJ hdGjI GdcaQI GddFGe cGf Pdc gh GdHGYK Ydi JSWjQ gPg GdQSGdI s
(3BNQgG (B:s
(3hEfeG WhdJ GdJCdja ef eKdiMjf NdJ GdOjGQ agh ef GdOdjd Ydi EfbQGV GdYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B282 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3c (B496) s
Keywords: (3GdJGQjNs